Pengaruh Edukasi terhadap Pengetahuan Orang Tua tentang TB Anak di Poli Anak Rumah Sakit Cut Meutia - Ajeng Dwi Syafira; Mardiati Mardiati; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2025)
Tuberculosis is a disease infection caused by Micobacterium Tuberculosisis disease with high level morbiditiy and very easy spread throug the droplet carried by air. Disease this could attack all age which children nor mature. There were 845.000 TB case in Indonesia in March 2021 and Lhokseumawe accounted for 10% of the number of cases in the province Aceh. Study this arm for analyze parental knowledge child TB patient before and after education at Cut Meutia Hospital Aceh Utara. This reasearch is Quasi Experimental reasearch type One-Group Pretest Posttest to 20 respondents who are parents from child TB patients. The sample is taken using accidental sampling. Measurement were carried out using a questionnaire containing the children`s TB knowledge. The results of this study indicate that majority of respondents before beiong given education had a sufficient level of knowledge as much as 80% and increased to good as much as 90% after being education. Data analysis using Wilcoxon test. The results of statistical analysis show p value < 0.05. the conclusion of this study is there is differences in the level of knowledge of parents before and after being given education about TB in children at Cut Meutia Hospital.